2004
DOI: 10.1063/1.1810512
|View full text |Cite
|
Sign up to set email alerts
|

Action spectroscopy and temperature diagnostics of H3+ by chemical probing

Abstract: Infrared absorption spectroscopy of few hundred H+(3) ions trapped in a 22-pole ion trap is presented using chemical probing as a sensitive detection technique down to the single ion level. By exciting selected overtone transitions of the (v(1)=0,v(2) (l)=3(1))<--(0,0(0)) vibrational band using an external cavity diode laser an accurate diagnostics measurement of the effective translational and rotational temperatures of the trapped ions was performed. The absolute accuracy of the measured transition frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 33 publications
2
64
0
Order By: Relevance
“…Such an experiment has been described recently by Mikosch et al (2004). In this work a 22-pole trap experiment has been devised to determine the rotational population of an H + 3 ensemble at T = 55 K by means of action spectroscopy.…”
Section: Laser Induced Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an experiment has been described recently by Mikosch et al (2004). In this work a 22-pole trap experiment has been devised to determine the rotational population of an H + 3 ensemble at T = 55 K by means of action spectroscopy.…”
Section: Laser Induced Reactionsmentioning
confidence: 99%
“…Experimentally this is very difficult. However, as described below, a method has been developed in recent years by Schlemmer et al (1999), Schlemmer et al (2002), Mikosch et al (2004), Schlemmer et al (2005), Asvany et al (2005a), and Asvany et al (2005b) to infer ro-vibrational spectra of a cloud of molecular ions in a trap experiment. Based on a few assumptions the rotational population of the ion cloud can be derived.…”
Section: Introductionmentioning
confidence: 99%
“…Multipole radiofrequency ion traps [1], in particular the 22-pole ion trap [2], are versatile devices used in laser spectroscopy [3,4,5,6,7,8,9,10] and investigations of chemical reaction processes [2,11,12,13] of atomic and molecular ions. High order multipole traps offer a large field free region in the trap center, and therefore provide a reduced interaction time of the ions with the oscillating electric field compared to a quadrupole trap [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the last column the In a previous study [25] a much higher value (∼130 K) was found at the same nominal trap temperature. This large deviation was found to be dependent on the helium buffer gas density inside the trap which had been limited in the previous experiment due to impurities in the gas supply lines.…”
Section: Resultsmentioning
confidence: 95%
“…which has been used in a previous study to measure the population of single rotational states inside the cryogenic ion trap by inducing vibrational transitions of the third overtone of the bending mode (around ∼7 200 cm −1 ) with a diode laser [25,26]. In Fig.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%